Determinan Gaya Hidup Sehat Remaja Boarding School dan Non Boarding School - Ridha Fitri; Asniar Asniar; Syarifah Rauzatul Jannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to look at the dominant differences in healthy lifestyles in Islamic boarding schools and non-Islamic boarding schools in Johan Pahlawan District, West Aceh Regency. The research method used is quantitative research with the analytical survey. The results of the bivariate test showed that there was a difference in a healthy lifestyle (0.047 < 0.05), there was no difference in BMI (0.474 > 0.05), there was a difference in psychological well-being (0.025 < 0.05), and there was a difference in life satisfaction (0.01 < 0,05) in pesantren and non-Islamic boarding schools. At the same time, in the multivariate test, the dominant determinant of a healthy lifestyle is life satisfaction where the p-value (0.00 < 0.05). In conclusion, there are differences in a healthy lifestyle, psychological well-being, and life satisfaction in boarding and non-boarding adolescents, with the dominant factor being life satisfaction. Keywords: Boarding, Healthy Lifestyle, Non-Boarding, Youth